O leitor universitário e a construção das práticas de ler e escrever textos impressos e digitais - Silva, Maria da Guia (2013)
The construction of a mapping of the practices of reading and writing printed and digital texts, declared by graduating students from the Bachelor s degree in Science and Technology (BCT), has provided us the analysis of the course they are making in such a socio-historical moment characterized by the revolution of the post-paper. In this sense, the general objective of this research is to understand how that construction works under the point of view of those graduating students. For this, our reflection has been guided by the search of answers for some questions which have presented to us: what reading and writing conceptions BCT graduating students have; what reading and writing practices those collaborators develop; what collections they declare to have access to; what differences they declare to have between printed and digital reading and writing along the different social roles they develop; what the reader/writer identity relations of those collaborators are. To achieving the plausible answers, we have gathered a corpus composed by texts of three genres of the argument order: academic profiles (or self-portrait), opinion articles and argumentative letters. Besides, we have made semi-structured interviews and questionnaires in the online tool of the Google Docs. The methodology which supports this academic work is the qualitative research (SIGNORINI; CAVALCANTI, 1998)of ethnographic direction (THOMAS, 1993; ANDRÉ, 1995) in Applied Linguistics (CELANI, 2000; MOITA-LOPES, 2006) and the theoretical contribution comes from the bakhtinian perspective of language conception (BAKHTIN [1929] 1981); the socio-historical writing construction (LÉVY, 1996; CHARTIER, R., 1998, 2002, 2007; COSCARELLI, 2006; CHARTIER, A., 2007; ARAÚJO, 2007; COSCARELLI; RIBEIRO, 2007; XAVIER, 2009; MARCUSCHI; XAVIER, 2010); from the studies of the pedagogy of the writing (GIROUX, 1997); from the literacy studies understood as sociocultural practice, plural and situated (TFOUNI, 1988; KLEIMAN, 1995; TINOCO, 2003, 2008; OLIVEIRA; KLEIMAN, 2008), from the studies about identity in postmodernity (HALL, 2003; BAUMAN, 2005). The results of the analysis have pointed at a multiplicity of reading/writing practices of printed and digital texts developed by the BCT graduating students due to the coexistence of the modality printed and that one derived from the new mobile devices. In that multiplicity, the prevalent idea of the collaborators is that there is a continuum between printed texts and digital texts (not a dichotomy), since the option of reading/writing printed texts or digital ones is always linked to specific communication situations, which involve participants, objectives, strategies, values, (dis)advantages, besides (re)creation of discursive genres in function of the mobile devices to which those collaborators have access in the different spheres of activities that they participate. All of that has caused a deep intersection in the identity traces of college students readers/writers in the 21st century which cannot be ignored by academic formation